Relationship of fractional exhaled nitric oxide with blood eosinophilia in characterizing type-2 airway inflammation in treatment-naïve patients with chronic obstructive pulmonary disease - Riksoam Chatterjee; Mansi Gupta; Zia Hashim; Ajmal Khan; Alok Nath; Vikas Aggarwal (Monaldi Archives for Chest Disease)
Fractional exhaled nitric oxide (FeNO), a sensitive and reproducible, non-invasive biomarker for type-2 (T2) inflammation in asthma, remains underutilized in chronic obstructive pulmonary disease (COPD). We investigated the potential role of FeNO and its relationship with blood eosinophilia in characterizing T2 airway inflammation in COPD. A single-center prospective observational study was conducted in 75 treatment-naïve adult patients with stable COPD and 75 age-sex-matched controls. The Global Initiative for Chronic Obstructive Lung Disease criteria were used for the diagnosis of COPD. FeNO levels were compared with clinico-radiological features, pulmonary functions, and other markers of T2 inflammation in COPD. Participants in the COPD subgroup had a median age of 62 (55.0, 69.0) years with a male predominance (77.3%). The median FeNO value was 27.0 ppb (19.0, 39.0) in COPD and 14.0 ppb (10.0, 20.0) in controls (p<0.001). FeNO values were categorized as low (≤25 ppb), intermediate (25-50 ppb), and high (≥50 ppb), with 57.3% of COPD patients having intermediate to high FeNO. In contrast, 46.7% of these patients had an absolute eosinophil count (AEC) ≥300/mm³. Higher values of FeNO in COPD were associated with the history of atopy (p<0.001), a positive bronchodilator reversibility on spirometry (p<0.05), and high-resolution computed tomography findings such as emphysema, bronchial wall thickening, bronchiectasis/bronchiolectasis, and mosaic attenuation (p<0.05). In addition, FeNO levels showed a strong positive linear correlation with serum immunoglobulin E (IgE) levels (r²=0.66, p<0.001) and AEC (r²=0.56, p<0.001). FeNO's best diagnostic cut-off level to detect T2 inflammation was 31 ppb (sensitivity: 65.9%, specificity: 86.5%; area under the receiver operating characteristic curve: 0.79). FeNO measurement, besides blood eosinophilia, is an effective, direct, airway-specific, non-invasive tool for detecting T2 airway inflammation in stable patients with COPD. Atopy (IgE sensitization) is a crucial factor in explaining higher FeNO values in COPD patients. FeNO correlates well with blood eosinophilia in COPD patients with an eosinophilic phenotype as a surrogate biomarker with good sensitivity and specificity.